Development and Pilot Test of the Workplace Readiness Questionnaire, a Theory-Based Instrument to Measure Small Workplaces’ Readiness to Implement Wellness Programs - Hannon, Peggy A.; Helfrich, Christian D.; Chan, K. Gary; Allen, Claire L.; Hammerback, Kristen; Kohn, Marlana J.; Parrish, Amanda T.; Weiner, Bryan J.; Harris, Jeffrey R. (American journal of health promotion, 2017)
Purpose. To develop a theory-based questionnaire to assess readiness for change in small workplaces adopting wellness programs. Design. In developing our scale, we first tested items via “think-aloud” interviews. We tested the revised items in a cross-sectional quantitative telephone survey. Setting. The study setting comprised small workplaces (20–250 employees) in low-wage industries. Subjects. Decision-makers representing small workplaces in King County, Washington (think-aloud interviews, n = 9), and the United States (telephone survey, n = 201) served as study subjects. Measures. We generated items for each construct in Weiner’s theory of organizational readiness for change. We also measured workplace characteristics and current implementation of workplace wellness programs. Analysis. We assessed reliability by coefficient alpha for each of the readiness questionnaire subscales. We tested the association of all subscales with employers’ current implementation of wellness policies, programs, and communications, and conducted a path analysis to test the associations in the theory of organizational readiness to change. Results. Each of the readiness subscales exhibited acceptable internal reliability (coefficient alpha range, .75–.88) and was positively associated with wellness program implementation (p < .05). The path analysis was consistent with the theory of organizational readiness to change, except change efficacy did not predict change-related effort. Conclusion. We developed a new questionnaire to assess small workplaces’ readiness to adopt and implement evidence-based wellness programs. Our findings also provide empirical validation of Weiner’s theory of readiness for change.